Perovskite solar cell based on polymer passivation
By adding polymers to the light-absorbing layer of perovskite solar cells, the problem of low stability of perovskite solar cells is solved, the photoelectric conversion efficiency and stability are significantly improved, and the efficiency and reliability of perovskite solar cells are improved.
Patent Information
- Application Number
- CN202510216107.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-26
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-02-26
AI Technical Summary
Perovskite solar cells have low stability and are susceptible to moisture, oxygen and ultraviolet rays, resulting in a decline in photoelectric performance. At the same time, some perovskite materials have a risk of environmental pollution, which limits their commercial applications.
The photoelectric conversion efficiency and stability of perovskite solar cells are improved by adding polymers, especially polymers contained in phenolphthalein and its derivative functional groups, in the light-absorbing layer of perovskite solar cells.
The photoelectric conversion efficiency and stability of perovskite solar cells have been significantly improved, the efficiency of formal devices has been improved by 21.11%, the efficiency of trans devices has been improved by 11.23%, and the long-term stability of the device has been improved.
Smart Images

Figure CN119836110A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cells, and in particular to a polymer passivated perovskite solar cell. Background Art
[0002] The application of perovskite materials in the field of solar cells is one of the most significant research directions in recent years. Since perovskite solar cells were first proposed in 2009, they have quickly become a hot field in photovoltaic research. Perovskites have been widely used in solar cells, photodetectors, lasers and other fields in recent years due to their excellent photoelectric properties, good thermal stability and low-cost manufacturing process. Especially in the field of perovskite solar cells, perovskite materials are a potential material to replace silicon-based solar cells. Compared with traditional silicon-based solar cells, perovskite solar cells have higher photoelectric conversion efficiency and lower production costs. In particular, perovskite materials have a very strong light absorption capacity and can effectively absorb most of the energy in the solar spectrum, thereby significantly improving the performance of the battery and attracting the attention of a large number of researchers and companies.
[0003] Although the efficiency of perovskite solar cells has approached or exceeded that of traditional silicon-based solar cells, their stability remains a key issue that needs to be addressed. Perovskite materials are easily affected by moisture, oxygen and ultraviolet rays, which leads to the degradation of their photoelectric performance. In addition, some perovskite materials (such as lead-containing perovskites) have environmental pollution risks, which limits the promotion of their commercial applications. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a polymer-passivated perovskite solar cell, which improves the photoelectric conversion efficiency and stability of the perovskite solar cell by adding a polymer.
[0005] The present invention adopts the following technical solution:
[0006] 1. A polymer-passivated perovskite solar cell
[0007] The perovskite solar cell is a formal perovskite solar cell or an inverted perovskite solar cell, and the perovskite solar cell comprises a conductive glass substrate layer, a core layer and a metal electrode layer; the core layer is arranged between the conductive glass substrate layer and the metal electrode layer; the core layer comprises an electron transport layer, a light absorption layer, a modification layer and a hole transport layer; the core layer of the formal perovskite solar cell is mainly composed of an electron transport layer, a light absorption layer, a modification layer and a hole transport layer arranged in sequence from bottom to top; the core layer of the inverted perovskite solar cell is mainly composed of a hole transport layer, a light absorption layer, a modification layer and an electron transport layer arranged in sequence from bottom to top.
[0008] The light absorbing layer contains a polymer, and the polymer structure has phenolphthalein and its derivative functional groups, and the structural formula of the polymer is:
[0009]
[0010] In the structural formula, R is -O, -NH, -N-(CH 2 ) n -SO 3 H and -N-(CH 2 ) n -NH 2 One of them.
[0011] The light-absorbing layer of the formal perovskite solar cell is mainly composed of a perovskite light-absorbing layer I, and the perovskite light-absorbing layer I is mainly coated with a precursor solution I; the light-absorbing layer of the inverted perovskite solar cell is mainly composed of one of a perovskite light-absorbing layer II and a perovskite light-absorbing layer III, and the perovskite light-absorbing layer II is mainly coated with a precursor solution II, and the perovskite light-absorbing layer III is mainly coated with a precursor solution III.
[0012] The precursor solution I contains a polymer with a mass concentration of 0.1-0.9 mg / mL and lead iodide or lead bromide (PbBr) with a molar concentration of 1.2-1.6 mol / mL. 2 ), the solvent of the precursor solution I is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, preferably, the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 8-9:2-1;
[0013] The precursor solution II contains a polymer with a mass concentration of 0.3-1.0 mg / mL, lead iodide with a molar concentration of 1.2-1.7 mol / mL, formamidine hydroiodide with a molar concentration of 2.0-2.5 mol / mL, methylamine hydrochloride with a molar concentration of 0.3-0.5 mol / mL, cesium iodide with a molar concentration of 0.15-0.19 mol / mL, methylamine hydrobromide with a molar concentration of 0.12-0.15 mol / mL, and lead bromide with a molar concentration of 0.13-0.19 mol / mL. The solvent of the precursor solution II is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide. Preferably, the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 3.5-4:1-1.5.
[0014] The precursor solution III contains a polymer with a mass concentration of 0.1-0.5 mg / mL, lead iodide with a molar concentration of 1.5-1.8 mol / mL, formamidine hydroiodide with a molar concentration of 0.8-1.0 mol / mL, methylamine hydrochloride with a molar concentration of 0.2-0.4 mol / mL, cesium iodide with a molar concentration of 0.05-0.1 mol / mL, and methylamine hydroiodide with a molar concentration of 0.15-0.18 mol / mL. The solvent of the precursor solution III is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide. Preferably, the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 4-5:0.9-1.
[0015] A modification layer is provided between the functional layer of the formal perovskite solar cell and the hole transport layer, and a modification layer is provided between the functional layer of the inverse perovskite solar cell and the electron transport layer;
[0016] The modification layer of the regular perovskite solar cell is mainly formed by spin coating of modification layer stock solution I, and the modification layer of the inverted perovskite solar cell is mainly formed by spin coating of modification layer stock solution II or modification layer stock solution III.
[0017] The modified layer stock solution I is a modified layer material I with a concentration of 2-6 mg / mL, and the modified layer material I contains 1-4.5 mg / mL of phenethylamine hydroiodide (PEAI) or a phenethylamine hydroiodide derivative, wherein the phenethylamine hydroiodide derivative includes one or more phenethylamine hydroiodide derivatives in which the hydrogen atoms on the benzene ring are replaced by halogen elements, such as p-fluorophenethylamine iodide (pF-PEAI), o-fluorophenethylamine iodide (oF-PEAI) and m-fluorophenethylamine iodide (mF-PEAI);
[0018] The modified layer stock solution II is a modified layer material II with a concentration of 2-4 mg / mL, and the modified layer material II contains phenylethylamine hydroiodide (PEAI) or octylamine hydroiodide (OAI) or a phenylethylamine hydroiodide derivative, and the phenylethylamine hydroiodide derivative includes one or more phenylethylamine hydroiodide derivatives in which the hydrogen atoms on the benzene ring are replaced by halogen elements, such as p-fluorophenylethylamine iodide (pF-PEAI), o-fluorophenylethylamine iodide (oF-PEAI) and m-fluorophenylethylamine iodide (mF-PEAI);
[0019] The modified layer stock solution III is a modified layer material III with a concentration of 1-4 mg / mL, and the modified layer material III contains phenylethylamine hydroiodide (PEAI) or octylamine hydroiodide (OAI) or phenylethylamine hydroiodide derivatives, and the phenylethylamine hydroiodide derivatives include one or more phenylethylamine hydroiodide derivatives in which the hydrogen atoms on the benzene ring are replaced by halogen elements, such as p-fluorophenylethylamine iodide (pF-PEAI), o-fluorophenylethylamine iodide (oF-PEAI) and m-fluorophenylethylamine iodide (mF-PEAI).
[0020] The material of the conductive glass substrate layer contains fluorine-doped tin oxide (FTO) or indium tin oxide (ITO), the material of the metal electrode layer contains molybdenum trioxide and silver, the material of the electron transport layer of the formal perovskite solar cell contains tin oxide, the material of the hole transport layer of the formal perovskite solar cell contains 4-tert-butylpyridine (tBP), bis(trifluoromethane)sulfonyl imide lithium salt (Li-TFSI) and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), the electron transport layer of the inverse perovskite solar cell contains phenyl C-61 butyric acid methyl ester (PCBM), and the material of the hole transport layer of the inverse perovskite solar cell contains nickel oxide.
[0021] 2. A method for preparing perovskite solar cells based on polymer passivation
[0022] The preparation method comprises the following steps:
[0023] When preparing a formal perovskite solar cell:
[0024] S1, coating an electron transport layer on the conductive glass substrate layer;
[0025] S2, coating a light absorbing layer of a formal perovskite solar cell on the electron transport layer described in S1;
[0026] S3, coating a modifying layer on the light absorbing layer described in S2;
[0027] S4, coating a hole transport layer on the modified layer described in S3;
[0028] S5, evaporating a metal electrode layer on the hole transport layer described in S4 to obtain the formal perovskite solar cell;
[0029] In step S1, coating the electron transport layer specifically comprises: 2 The colloidal aqueous solution was subjected to ultrasonic treatment for 10-30 min and then filtered. 2 The solution is spin-coated on the FTO or ITO surface and then annealed. 2 The colloidal aqueous solution is 12% SnO 2 The solution is mixed with deionized water in a volume ratio of 3:1; preferably, the solution is filtered after ultrasonic treatment for 20 minutes, and annealed on a hot stage at 150° C. for 30 minutes to complete the preparation of the electron transport layer.
[0030] In the step S2, coating the light-absorbing layer of the formal perovskite solar cell is specifically as follows: adding an N,N-dimethylformamide solution containing a polymer and lead iodide to dimethyl sulfoxide to prepare a precursor solution I, spin-coating the precursor solution I on the electron transport layer, and then sequentially performing pre-annealing, dripping an organic cation solution and annealing to form a perovskite light-absorbing layer I on the electron transport layer, thereby forming the light-absorbing layer of the formal perovskite solar cell; the precursor solution I contains a polymer with a mass concentration of 0.1-0.9 mg / mL and lead iodide or lead bromide with a molar concentration of 1.2-1.6 mol / mL, and the solvent of the precursor solution I is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide.
[0031] The organic cation solution contains formamidine hydroiodide (FAI), methylamine hydroiodide (MAI) with a mass concentration of 5-10 mg / mL, and methylamine hydrochloride (MACl) with a mass concentration of 5-10 mg / mL; the solvent of the organic cation solution is isopropyl alcohol (IPA), and the organic cation solution also contains at least one of methylamine hydrobromide (MABr), cesium iodide (CsI) and formamidine hydrochloride (FACl).
[0032] The conditions for spin coating on the electron transport layer are: the speed of the coating machine is 3000-5000 r / min, and the time is 20-40s; the conditions for spin coating on the hole transport layer are: the speed of the coating machine is 3000-4000 r / min, and the time is 25-40s.
[0033] In the step S3, coating the modifying layer on the light absorbing layer specifically comprises: coating a modifying layer stock solution I on the light absorbing layer to form the modifying layer; the modifying layer stock solution I comprises a modifying layer material I, and the modifying layer material I comprises phenethylamine hydroiodide (PEAI) or a phenethylamine hydroiodide derivative, and the phenethylamine hydroiodide derivative comprises one or more phenethylamine hydroiodide derivatives such as pF-PEAI, oF-PEAI and mF-PEAI, in which the hydrogen atoms on the benzene ring are replaced by halogen elements.
[0034] When preparing inverse perovskite solar cells:
[0035] D1, coating a hole transport layer on the conductive glass substrate layer;
[0036] D2, coating a light absorbing layer of an inverse perovskite solar cell on the hole transport layer described in D1;
[0037] D3, coating a modifying layer on the light absorbing layer described in D2;
[0038] D4, coating an electron transport layer on the modified layer described in D3;
[0039] D5. Vapor-depositing a metal electrode layer on the hole transport layer described in D1 to obtain the inverse perovskite solar cell.
[0040] In the step D1, coating the hole transport layer is specifically as follows: x The solution was ultrasonically treated for 10-30 min and then filtered. x The solution is spin-coated on the FTO or ITO surface, or the SAM solution is spin-coated on the FTO or ITO surface, and then annealed; the NiO x The concentration of the solution is 10 mg / mL, and the concentration of the SAM solution is 1 mg / mL. Preferably, NiO x The solution was ultrasonically treated for 20 min and then filtered. x The solution is spin-coated on the FTO or ITO surface and annealed on a hot plate at 180° C. for 15 minutes to complete the preparation of the hole transport layer; or the SAM solution is spin-coated on the FTO or ITO surface and annealed on a hot plate at 100° C. for 10 minutes to complete the preparation of the hole transport layer.
[0041] In the step D2, coating the light-absorbing layer of the inverse perovskite solar cell is specifically: spin coating the precursor solution II or the precursor solution III on the hole transport layer, then dripping the anti-solvent solution and annealing, forming the perovskite light-absorbing layer II or the perovskite light-absorbing layer III on the hole transport layer, and then forming the light-absorbing layer of the inverse perovskite solar cell; the precursor solution II contains a polymer with a mass concentration of 0.3-1.0 mg / mL, lead iodide with a molar concentration of 1.2-1.7 mol / mL, formamidine hydroiodide with a molar concentration of 2.0-2.5 mol / mL, methylamine hydrochloride with a molar concentration of 0.3-0.5 mol / mL, cesium iodide with a molar concentration of 0.15-0.19 mol / mL, and cesium iodide with a molar concentration of 0.12-0.1 5mol / mL methylamine hydrobromide and 0.13-0.19mol / mL lead bromide, the solvent of the precursor solution II is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide; the precursor solution III contains a polymer with a mass concentration of 0.1-0.5mg / mL, lead iodide with a molar concentration of 1.5-1.8mol / mL, formamidine hydroiodide of 0.8-1.0mol / mL, methylamine hydrochloride of 0.2-0.4mol / mL, cesium iodide of 0.05-0.1mol / mL and methylamine hydroiodide of 0.15-0.18mol / mL, and the solvent of the precursor solution III is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide.
[0042] The anti-solvent solution is one of chlorobenzene, anisole and ether.
[0043] The conditions for spin coating on the hole transport layer are: the speed of the coater is 1000-2000r / min, the time is 5-10s, 4000-5000r / min, the time is 20-35s, and the conditions for spin coating on the electron transport layer are: the speed of the coater is 1000-2000r / min, the time is 20-40s; the time for adding the anti-solvent is 5-10s before the end of the rotation; the temperature of the pre-annealing is 60-80°C, the time is 30s-90s; the temperature of the re-annealing is 90-110°C, the time is 15min-30min.
[0044] In the step D3, coating the modifying layer on the light absorbing layer specifically comprises: coating a modifying layer stock solution II or a modifying layer stock solution III on the light absorbing layer to form the modifying layer; the modifying layer stock solution II comprises a modifying layer material II, and the modifying layer material II comprises phenethylamine hydroiodide or octylamine hydroiodide or a phenethylamine hydroiodide derivative, and the phenethylamine hydroiodide derivative comprises one or more of p-fluorophenethylamine iodine, o-fluorophenethylamine iodine and m-fluorophenethylamine iodine; the modifying layer stock solution III comprises a modifying layer material III, and the modifying layer material III comprises phenethylamine hydroiodide or octylamine hydroiodide or a phenethylamine hydroiodide derivative, and the phenethylamine hydroiodide derivative comprises one or more of p-fluorophenethylamine iodine, o-fluorophenethylamine iodine and m-fluorophenethylamine iodine.
[0045] The beneficial effects of the present invention are as follows:
[0046] 1. The present invention is aimed at the research on the passivation of defects in the perovskite light absorption layer. Based on the preparation of formal or inverted perovskite solar cells, only polymers are added to the precursor solution. The photoelectric conversion efficiency of the formal device is increased by 21.11% compared with the standard device, and the inverted device is increased by 11.23% compared with the standard device, which greatly improves the device efficiency and stability.
[0047] 2. The present invention can reduce surface defects through coordination by using the functional groups of phenolphthalein and its derivatives in the polymer structure. The long polymer chain enables the perovskite precursor to nucleate uniformly in the film, thereby improving the photoelectric conversion efficiency and stability of the device. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 It is a structural diagram of various polymers in the present invention.
[0049] Figure 2 1 is a structural diagram of polymer 1, polymer 2 and polymer 3 used in the examples of the present invention.
[0050] Figure 3 It is a JV curve diagram of the perovskite solar cell obtained in Example 1 of the present invention and Comparative Example 1.
[0051] Figure 4This is a stability test diagram of the perovskite solar cell obtained in Example 1 of the present invention and Comparative Example 1.
[0052] Figure 5 It is a JV curve diagram of the perovskite solar cell obtained in Example 2 of the present invention and Comparative Example 2.
[0053] Figure 6 This is a stability test diagram of the perovskite solar cell obtained in Example 2 of the present invention and Comparative Example 2.
[0054] Figure 7 It is a JV curve diagram of the perovskite solar cell obtained in Example 3 of the present invention and Comparative Example 3.
[0055] Figure 8 This is a stability test diagram of the perovskite solar cell obtained in Example 3 of the present invention and Comparative Example 3. DETAILED DESCRIPTION
[0056] All technical and scientific terms used herein are consistent with the meanings commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for describing specific embodiments and are not intended to limit the present invention. The singular forms of "a", "said" and "the" used in the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0057] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or purchased commercially.
[0058] Embodiments of the present invention are as follows:
[0059] In an embodiment of the present invention, the polymer is derived from Figure 1 Any one of the following, the structural formula is Figure 1 (a) and (b), where R can be -O, -NH, -N-(CH 2 ) n -SO 3 H,-N-(CH 2 ) n -NH 2 Any group (n=0 to 20).
[0060] Specifically, select the structural formula such as Figure 2 (a) Polymer 1, (b) Polymer 2 and (c) Polymer 3 are shown.
[0061] Example 1
[0062] In this example, a precursor solution I containing a polymer 1 solution with a mass concentration of 0.35 mg / mL is used to prepare a formal perovskite solar cell. The light absorption layer of the perovskite solar cell obtained in this example is mainly composed of the perovskite light absorption layer I.
[0063] The specific steps are as follows:
[0064] Step 1: After washing the ITO conductive glass with deionized water, isopropanol and ethanol solution in sequence, blow it dry with nitrogen and treat it with ultraviolet ozone instrument for 20 minutes. 2 The solution was mixed with deionized water in a volume ratio of 4:1 and ultrasonically treated for 20 min. 2 It was spin-coated on the ITO surface and annealed on a hot plate at 150°C for 30 min to form an electron transport layer.
[0065] Step 2: Weigh 0.35 mg of polymer 1 and dissolve it in DMF. Prepare 1.5 M PbI 2 Dissolved in 900 μL of DMF (containing polymer 1 at a concentration of 0.35 mg / mL) and 100 μL of DMSO, stirred and dissolved for 12 hours, filtered to obtain precursor solution I, spin-coated on the surface of the electron transport layer, the speed of the gelator was 1700 r / min, and pre-annealed on a hot plate at 75°C for 45 seconds after 30 seconds. After that, the substrate was restored to room temperature, and an organic cation solution was added dropwise to the center of the perovskite substrate. The organic cation was prepared by dissolving 90 mg of FAI, 6.4 mg of MAI and 9 mg of MACl in 1 mL of isopropanol IPA; the substrate was placed on a hot plate at 150°C for annealing for 10 minutes to form a perovskite light absorption layer I.
[0066] Step 3: spin-coat an octylamine hydroiodide (OAI) modification layer with a concentration of 1.5 mg / mL on the surface of the substrate.
[0067] In step 4, an acetonitrile solution containing 4-tert-butylpyridine (TBP) and Li-TFSI and a chlorobenzene solution of Spiro-OMeTAD are spin-coated on the perovskite substrate as a hole transport layer.
[0068] Step 5, placing the substrate in an evaporator, first evaporating 4.5 nm of molybdenum trioxide, and then evaporating 80 nm of silver as a back electrode.
[0069] Example 2
[0070] In this example, a precursor solution II containing a polymer 2 solution with a mass concentration of 0.9 mg / mL is used to prepare an inverted perovskite solar cell. The light absorption layer of the perovskite solar cell obtained in this example is mainly composed of a perovskite light absorption layer II.
[0071] The specific steps are as follows:
[0072] Step 1: After washing the ITO conductive glass with deionized water, isopropanol and ethanol solution in sequence, blow it dry with nitrogen and treat it with a UV ozone instrument for 20 minutes. x The solution was spin-coated on the ITO surface and annealed on a hot plate at 180°C for 15 min to form a hole transport layer.
[0073] Step 2: Weigh 0.9 mg of polymer 2 and dissolve it in 1 mL of DMF. Filter it after it is completely dissolved. Then prepare perovskite precursor solution II, solution A: weigh 1135.99 mg of PbI 2 , 385.07 mg FAI, 30.24 mg MACl were dissolved in 1.28 mL DMF (containing 0.9 mg / mL polymer 1) and 0.32 mL DMSO; Solution B: 15.66 mg MABr and 56.53 mg PbBr 2 Dissolve in 80μL DMF and 20μL DMSO; Solution C: Weigh 45.38mg CsI and dissolve in 100μL DMSO. Stir and dissolve A, B and C solutions for 12h and mix them to obtain precursor solution II. Spin-coat precursor solution II on the surface of the hole transport layer at a speed of 1000r / min, 10s and 5000r / min, 30s. Add chlorobenzene antisolvent in the last 5s and anneal on a hot plate at 100℃ for 30min. After that, the substrate is restored to room temperature to form the perovskite light absorption layer II.
[0074] Step 3: spin-coat a phenylethylamine hydroiodide (PEAI) modification layer with a concentration of 2.4 mg / mL on the surface of the substrate.
[0075] Step 4: spin-coat 20 mg / mL PCBM on the surface of the substrate as a hole transport layer.
[0076] Step 5, placing the substrate in an evaporator and evaporating 80 nm of silver as a back electrode.
[0077] Example 3
[0078] In this example, a reverse perovskite solar cell is prepared using a precursor solution III containing a polymer 3 solution with a mass concentration of 0.5 mg / mL. The light absorption layer of the perovskite solar cell obtained in this example is mainly composed of a perovskite light absorption layer III.
[0079] The specific steps are as follows:
[0080] Step 1: After washing the ITO conductive glass with deionized water, isopropanol and ethanol solution in sequence, the glass was dried with nitrogen and treated with a UV ozone instrument for 20 minutes. 1 mg / mL SAM was spin-coated in a glove box and annealed at 100° C. for 10 minutes to form a hole transport layer.
[0081] Step 2: Weigh 0.5 mg of polymer 3 and dissolve it in 1 mL of DMF solution. Filter it after it is completely dissolved. Then prepare perovskite precursor solution III: Weigh 1452 mg of PbI 2 438.6 mg of FAI, 30 mg of MACl, 39 mg of CsI and 47.8 mg of MAI were dissolved in 1.49 mL of DMF (containing 0.5 mg / mL of polymer 1) and 0.31 mL of DMSO, stirred and dissolved for 12 hours, and then mixed to obtain precursor solution III. Precursor solution III was spin-coated on the surface of the hole transport layer, with a spin coater speed of 1000 r / min for 10 seconds, 5000 r / min for 30 seconds, and anisole anti-solvent was added dropwise in the last 15 seconds, and annealed on a hot stage at 100°C for 15 minutes. After that, the substrate was restored to room temperature to form a perovskite light absorption layer III.
[0082] Step 3: spin-coat a 2 mg / mL phenylethylamine hydroiodide (PEAI) modification layer on the substrate surface.
[0083] Step 4: Spin-coat 15 mg / mL PCBM and 1 mg / mL BCP on the substrate surface as a hole transport layer.
[0084] Step 5, placing the substrate in an evaporator and evaporating 80 nm of silver as a back electrode.
[0085] Comparative Example 1
[0086] The difference between this comparative example and Example 1 is that in step 2, polymer 1 is not added to the perovskite precursor solution I.
[0087] Comparative Example 2
[0088] The difference between this comparative example and Example 2 is that in step 2, polymer 2 is not added to the perovskite precursor solution II.
[0089] Comparative Example 3
[0090] The difference between this comparative example and Example 3 is that in step 2, polymer 3 is not added to the perovskite precursor solution III.
[0091] The perovskite solar cells prepared by Examples 1 to 3 of the present invention and Comparative Examples 1 to 3 were respectively subjected to JV curve tests and stability tests. The test process and results are as follows:
[0092] The battery uses silver as the back battery. When performing the JV test, the instrument calibration and the assembly method of the formal / inverse perovskite solar cell device are: first calibrate the Keithley instrument using a standard silicon-based solar cell, then place the prepared battery in it, the back electrode contacts the probe in the test battery mold, and the positive and negative electrodes of the test battery mold are connected to the positive and negative electrodes of the calibrated Keithley instrument respectively. Given a voltage value of 1.2V, the battery is tested for the JV curve.
[0093] Figure 3 , Figure 5 and Figure 7 They are respectively the JV curves of the formal perovskite solar cell (Example 1) in which the perovskite precursor solution I contains 0.35 mg / mL of polymer 1 and the comparison sample (Comparative Example 1), the JV curves of the inverse perovskite solar cell (Example 2) in which the perovskite precursor solution II contains 0.9 mg / mL of polymer 2 and the comparison sample (Comparative Example 2), and the JV curves of the inverse perovskite solar cell (Example 3) in which the perovskite precursor solution II contains 0.5 mg / mL of polymer 3 and the comparison sample (Comparative Example 3).
[0094] from Figure 3 It can be seen that the photoelectric conversion efficiency of the formal perovskite solar cell prepared by adding polymer 1 to the perovskite precursor solution is the highest 23.12% (Example 1), and the corresponding current density Jsc, opening voltage Voc and filling factor FF are 24.73 mA / cm 2 , 1.146V and 81.08%. The photoelectric conversion efficiency of Example 1 is improved by 21.11% compared with that of Comparative Example 1.
[0095] from Figure 5 It can be seen that the photoelectric conversion efficiency of the inverse perovskite solar cell prepared by adding 0.9 mg / mL polymer 2 to the perovskite precursor solution is 23.61% (Example 2), and the corresponding current Jsc, opening voltage Voc and fill factor FF are 23.95 mA / cm 2 , 1.51V and 23.57%.
[0096] The photoelectric conversion efficiency of Example 3 is improved by 11.23% compared with that of Comparative Example 3.
[0097] from Figure 7 It can be seen that the photoelectric conversion efficiency of the inverse perovskite solar cell containing 0.5 mg / mL polymer 3 (Example 3) is the highest at 23.57%, and the corresponding current density Jsc, opening voltage Voc and fill factor FF are 23.95 mA / cm 2, 1.151V and 85.31%. The photoelectric conversion efficiency of Example 3 is improved by 11.23% compared with that of Comparative Example 3.
[0098] Figure 4 , Figure 6 and Figure 8 They are stability test graphs of a formal perovskite solar cell (Example 1) in which the perovskite precursor solution contains 0.35 mg / mL of polymer 1 and a control sample (Comparative Example 1), stability test graphs of an inverted perovskite solar cell (Example 2) in which the perovskite precursor solution contains 0.9 mg / mL of polymer 2 and a control sample (Comparative Example 2), and stability test graphs of an inverted perovskite solar cell (Example 3) in which the perovskite precursor solution contains 0.5 mg / mL of polymer 3 and a control sample (Comparative Example 3).
[0099] from Figure 4 , Figure 6 and Figure 8 It can be seen that the stability of perovskite solar cells has been improved by adding polymers.
[0100] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. It should be noted that for researchers in the field, the present invention is intended to cover any variation, use or adaptive change of the present application, which follows the general principles of the present application and includes common knowledge or conventional technical means in the technical field that are not disclosed in the present application.
Claims
1. A polymer-passivated perovskite solar cell, characterized in that: The perovskite solar cell is a formal perovskite solar cell or an inverted perovskite solar cell, and the perovskite solar cell comprises a conductive glass substrate layer, a core layer and a metal electrode layer; the core layer is arranged between the conductive glass substrate layer and the metal electrode layer; the core layer comprises an electron transport layer, a light absorption layer, a modification layer and a hole transport layer; the core layer of the formal perovskite solar cell is mainly composed of an electron transport layer, a light absorption layer, a modification layer and a hole transport layer arranged in sequence from bottom to top; the core layer of the inverted perovskite solar cell is mainly composed of a hole transport layer, a light absorption layer, a modification layer and an electron transport layer arranged in sequence from bottom to top.
2. A polymer-passivated perovskite solar cell according to claim 1, characterized in that: The light absorbing layer contains a polymer, and the polymer structure has phenolphthalein and its derivative functional groups, and the structural formula of the polymer is: In the structural formula, R is -O, -NH, -N-(CH2) n -SO3H and -N-(CH2) n -NH2 is one of them.
3. A polymer-passivated perovskite solar cell according to claim 2, characterized in that: The light-absorbing layer of the formal perovskite solar cell is mainly composed of a perovskite light-absorbing layer I, and the perovskite light-absorbing layer I is mainly coated with a precursor solution I.
4. A polymer-passivated perovskite solar cell according to claim 3, characterized in that: The precursor solution I contains a polymer with a mass concentration of 0.1-0.9 mg / mL and lead iodide or lead bromide with a molar concentration of 1.2-1.6 mol / mL. The solvent of the precursor solution I is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, and the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 8-9:2-1.
5. A polymer-passivated perovskite solar cell according to claim 2, characterized in that: The light-absorbing layer of the inverted perovskite solar cell is mainly composed of one of a perovskite light-absorbing layer II and a perovskite light-absorbing layer III. The perovskite light-absorbing layer II is mainly coated with a precursor solution II, and the perovskite light-absorbing layer III is mainly coated with a precursor solution III.
6. A polymer-passivated perovskite solar cell according to claim 5, characterized in that: The precursor solution II contains a polymer with a mass concentration of 0.3-1.0 mg / mL, lead iodide with a molar concentration of 1.2-1.7 mol / mL, formamidine hydroiodide with a molar concentration of 2.0-2.5 mol / mL, methylamine hydrochloride with a molar concentration of 0.3-0.5 mol / mL, cesium iodide with a molar concentration of 0.15-0.19 mol / mL, methylamine hydrobromide with a molar concentration of 0.12-0.15 mol / mL, and lead bromide with a molar concentration of 0.13-0.19 mol / mL. The solvent of the precursor solution II is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, and the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is 3.5-4:1-1.
5. The precursor solution III contains a polymer with a mass concentration of 0.1-0.5 mg / mL, lead iodide with a molar concentration of 1.5-1.8 mol / mL, formamidine hydroiodide with a molar concentration of 0.8-1.0 mol / mL, methylamine hydrochloride with a molar concentration of 0.2-0.4 mol / mL, cesium iodide with a molar concentration of 0.05-0.1 mol / mL, and methylamine hydroiodide with a molar concentration of 0.15-0.18 mol / mL. The solvent of the precursor solution III is a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide, and the volume ratio of the N,N-dimethylformamide to dimethyl sulfoxide is 4-5:0.9-1.
7. A polymer-passivated perovskite solar cell according to claim 1, characterized in that: The modification layer of the formal perovskite solar cell is mainly formed by spin coating of a modification layer stock solution I, wherein the modification layer stock solution I is a modification layer material I with a concentration of 2-6 mg / mL, and the modification layer material I contains 1-4.5 mg / mL of phenethylamine hydroiodide or a phenethylamine hydroiodide derivative, wherein the phenethylamine hydroiodide derivative includes one or more of p-fluorophenethylamine iodine, o-fluorophenethylamine iodine and m-fluorophenethylamine iodine.
8. The polymer-passivated perovskite solar cell according to claim 1, characterized in that: The modification layer of the inverse perovskite solar cell is mainly formed by spin coating of modification layer stock solution II or modification layer stock solution III; The modified layer stock solution II is a modified layer material II with a concentration of 2-4 mg / mL, and the modified layer material II contains phenethylamine hydroiodide or octylamine hydroiodide or a phenethylamine hydroiodide derivative, and the phenethylamine hydroiodide derivative includes one or more of p-fluorophenethylamine iodine, o-fluorophenethylamine iodine and m-fluorophenethylamine iodine; The modified layer stock solution III is a modified layer material III with a concentration of 1-4 mg / mL, and the modified layer material III contains phenethylamine hydroiodide or octylamine hydroiodide or a phenethylamine hydroiodide derivative, and the phenethylamine hydroiodide derivative includes one or more of p-fluorophenethylamine iodine, o-fluorophenethylamine iodine and m-fluorophenethylamine iodine.
9. A polymer-passivated perovskite solar cell according to claim 1, characterized in that: The material of the conductive glass substrate layer contains fluorine-doped tin oxide or indium tin oxide, and the material of the metal electrode layer contains molybdenum trioxide and silver.
10. The polymer-passivated perovskite solar cell according to claim 1, characterized in that: The material of the electron transport layer of the formal perovskite solar cell contains tin oxide, and the material of the hole transport layer of the formal perovskite solar cell contains 4-tert-butylpyridine, bis(trifluoromethane)sulfonyl imide lithium salt and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene; the electron transport layer of the inverse perovskite solar cell contains phenyl C-61 butyric acid methyl ester, and the material of the hole transport layer of the inverse perovskite solar cell contains nickel oxide.
Citation Information
Patent Citations
Preparation method of perovskite film
CN107302055A
Perovskite solar cell based on surfactant passivation and preparation method thereof
CN110518127A
Star polymer-doped perovskite solar cell and preparation method thereof
CN113637126A
Perovskite solar cell and preparation method thereof
CN115568237A
Perovskite solar cell and preparation method thereof
CN119300615A